ChemInform Abstract: Gold(I)‐Catalyzed Reactions of 1‐(ortho‐Alkynylaryl)ureas: Highly Selective Heterocyclization and Synthesis of Mixed N, O‐Acetals. Issue 31 (5th August 2014) - Gimeno, Ana; Cuenca, Ana B.; Medio‐Simon, Mercedes; Asensio, Gregorio
Abstract Treatment of alkynylureas (I) with trifluoroethanol in the presence of a Au/Ag catalytic system provides N‐6‐exo‐dig heterocyclization products (III) and in some cases open chain acetals as side products.